Islamic Considerations In Recognizing And Pricing Intellectual Assets - Sadeghzadeh, Akbar; Taghi Alavi, Seyyed Mohammad (Accounting Department,, 2005)
Intellectual property right (IPR), intellectual capital (IC), intellectual assets (IA) and the similar terminology are becoming more fashionable and gaining more importance and attraction as knowledge-based economy (KBE) takes over the traditional economy gradually. Although the ï¬eld ages about one centuryâ€˜, it still is not well-organized, hence is a very demanding discourse. The discipline is still immature and